Polycystic liver disease in children - Cresceri, Aída; Lizaso, Isabel; Wettstein, Juana; Chavarría, Oscar (Cirugía del Uruguay, 1993)
A case of hepatic polycystosis in a 4 year old child is presented. As regards the subject, a revision of the pathology is made, emphasizing the value of echography far preoperative diagnosis and declaring preference far fenestration procedure far cyst treatment.